2020
DOI: 10.1158/1538-7445.am2020-3453
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3453: Cancer Cell Line Factory: A systematic approach to create next-generation cancer model at scale

Abstract: Precision cancer medicine is based on the ability to predict the dependencies of a given tumor from its molecular makeup. Despite successes in multiple common cancers, such prediction remains challenging for the majority of rare and understudied tumors given the absence of laboratory model systems in which to discover and/or validate therapeutic hypotheses. Here, we describe our efforts to address this challenge systematically with the ultimate goal of making it possible to learn how to predict ex vivo growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One approach to understanding tumor dependencies is through genomewide genetic and chemical perturbation datasets (e.g., DEPMAP ( 7, 8 ), Project SCORE ( 9 ), and Connectivity Map ( 10 )) that have been paired with thousands of deeply characterized cancer models (e.g., Cancer Cell Line Encyclopedia ( 11 ), Cancer Cell Line Factory, ( 12 ), and Human Cancer Models Initiative ( 13 )). Multiple studies have demonstrated the ability of DEPMAP to translate gene essentially to novel therapeutic targets ( 14 – 18 ) and a broader functional understanding of tumor dependencies ( 19, 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to understanding tumor dependencies is through genomewide genetic and chemical perturbation datasets (e.g., DEPMAP ( 7, 8 ), Project SCORE ( 9 ), and Connectivity Map ( 10 )) that have been paired with thousands of deeply characterized cancer models (e.g., Cancer Cell Line Encyclopedia ( 11 ), Cancer Cell Line Factory, ( 12 ), and Human Cancer Models Initiative ( 13 )). Multiple studies have demonstrated the ability of DEPMAP to translate gene essentially to novel therapeutic targets ( 14 – 18 ) and a broader functional understanding of tumor dependencies ( 19, 20 ).…”
Section: Introductionmentioning
confidence: 99%